BODY IMAGE AND RELIGIOSITY IN ADOLESCENTS: A COMPARATION BETWEEN PUBLIC AND PRIVATE HIGH SCHOOL STUDENTS - WIDANA PRIMANINGTYAS; ANAK AGUNG ALIT KIRTI ASTUTI NARENDRA PUTRI; HENI HASTUTI (Smart Medical Journal, 2019)
ABSTRACTBackground: There are many literatures have reported the link between religiosity and health outcomes. Body image come as someones’ perceptions towards their body, also being influenced by religiosity. The aims of this study was to compare body image in adolescents between private (Islamic) and public (mix religion) high schools, beside the similar study in Indonesia have not yet reported. Method: This was a cross sectional design study using Body Shape Questionnaire (BSQ) and Duke University Religion (Durel) Index questionnaire. We used purposive sampling for sampling technique. The data collected from one private (I) and one public (II) senior high schools in Surakarta, Indonesia.  An independent-samples t test was conducted to compare the BSQ score and Durel index between both schools.  Result: Total 150 questionnaires were distributed to both schools, only 116 questionnaires filled completely. There was a significant difference in the Durel index between school I (M=25.90, SD=2.82) and II (M= 24.70, SD=1.55); t(114)= 2.84, p=0.005. But there was not a significant difference in the BSQ score between school I (M= 77.00, SD=26.16) and II (M= 79.86, SD=26.67); t(114)=-0.58, p=0.561. Conclusion: These results showed that the students who studying in a private senior high school have a higher religiosity compare to those who studying in public senior high school. The higher religiosity in private schools’ gave them lower score on BSQ compare to public schools’, but the mean differences were not statistically significant. Keywords: body image; adolescents; body shapeABSTRAKBackground: Religiusitas dan hubungannya dengan outcome kesehatan telah dibahas dalam berbagai studi. Salah satu outcome kesehatan yang berhubungan dengan religiusitas adalah body image. Tujuan dari studi ini adalah untuk membandingkan body image pada remaja di sekolah menengah atas privat (Islami) dan sekolah umum (berbagai agama). Studi ini di Indonesia masih belum banyak ditemukan publikasinya.Metode: Studi ini adalah studi observasional analitik dengan pendekatan cross sectional. Dua kuisioner digunakan sebagai alat ukur penelitian yaitu Body Shape Questionnaire (BSQ) dan Duke University Religion (Durel) Index questionnaire. Teknik sampling yang digunakan adalah purposive sampling. Data penelitian didapatkan dari 1 sekolah menengah atas privat (I) dan 1 umum (II) di Surakarta, Indonesia. Untuk analisis data dalam studi ini digunakan Independent-samples t test  untuk membandingkan skor BSQ dan Durel index dari dua sekolah tersebut.Hasil: 150 kuisioner didistribusikan kepada remaja di kedua sekolah, hanya 116 kuisioner yang pengisiannya lengkap. Terdapat perbedaan yang signifikan dari skor Durel index antara sekolah I (M=25.90, SD=2.82) dan II (M= 24.70, SD=1.55); t(114)= 2.84, p=0.005. Untuk skor BSQ antara sekolah I (M= 77.00, SD=26.16) dan II (M= 79.86, SD=26.67); t(114)=-0.58, p=0.561, ditemukan perbedaan mean, namun tidak signifikan secara statistik.Kesimpulan: Hasil dari studi ini dapat menggambarkan bahwa remaja yang bersekolah di sekolah menengah atas privat mempunyai religiusitas yang lebih tinggi daripada di sekolah umum. Remaja di sekolah privat dilihat dari nilai Mean, mempunyai hasil body image yang lebih baik berdasarkan skor BSQ dibandingkan dengan sekolah umum, namun tidak signifikan secara statistik.Keywords: body image; remaja; bentuk tubuh